Effects of episodic future thinking on discounting: Personalized age‐progressed pictures improve risky long‐term health decisions. Issue 1 (17th December 2015) - Kaplan, Brent A.; Reed, Derek D.; Jarmolowicz, David P.
Abstract : Many everyday choices are associated with both delayed and probabilistic outcomes. The temporal attention hypothesis suggests that individuals' decision making can be improved by focusing attention on temporally distal events and implies that environmental manipulations that bring temporally distal outcomes into focus may alter an individual's degree of discounting. One such manipulation, episodic future thinking, has shown to lower discount rates; however, several questions remain about the applicability of episodic future thinking to domains other than delay discounting. The present experiments examine the effects of a modified episodic‐future‐thinking procedure in which participants viewed age‐progressed computer‐generated images of themselves and answered questions related to their future, on probability discounting in the context of both a delayed health gain and loss. Results indicate that modified episodic future thinking effectively altered individuals' degree of discounting in the predicted directions and demonstrate the applicability of episodic future thinking to decision making of socially significant outcomes.